The Impact of Total Quality Management in the Supply Chain of High Schools on Performance: A Proposed Framework - Sami Abdullah Kadhim; Md. Fauzi Bin Ahmed (International Journal of Supply Chain Management, 2019)
Education plays a major role in the progress and development of any country and it helps raise equal opportunities and develop human resources. Education in Iraq suffers from many problems, including a lack of technology, school buildings, and school facilities, and a lack of training for principals and teachers. It is the responsibility of the ministry of education to tackle this situation and it can only possible when authority maintains its relationship with institutions. The supply chain is a flow of material, information, and finance. The ministry of education has to convey the material, information, and finance to the high school for their operations. After through literature review, it has been revealed that there is the significant relationship between TQM factors and performance. This study examines the application of TQM in the supply chain of schools. Therefore, the Iraq government is working to improve the quality of the flow of information, material, and finance in schools through the implementation of TQM. A number of previous studies have focused on the importance of implementing TQM in Iraqi schools for continuous improvement and eliminating the problems facing education. The aim of this study is to highlight the problem and propose a framework on the effects of TQM on performance. This framework needs empirical verification so for future study the data will be collected from the management of Iraqi schools. Base on literature review authors proposed framework of TQM. Habitually, it will assist high schools in improving their practices TQM.